1986
DOI: 10.1111/j.1365-2125.1986.tb02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Food induced changes in theophylline absorption from a once‐a‐day theophylline product.

Abstract: 1 Bioavailability and the absorption pattern of theophylline from the sustained release theophylline (SRT) product, Uniphyllin, were studied in eight adults and eight children under fasting conditions in the morning, after a standardised breakfast in the morning, and under fasting conditions in the evening (adults only). Theophylline given intravenously was used as a reference.2 The extent of absorption of theophylline was complete for all administrations of SRT both in adults and children.3 In adults the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Depending on the type of dosage form and the intraluminal conditions, a co-administered meal can result in both so-called "positive" and "negative" food effects. Positive food effects typically come along with an increase in drug release from ER formulations and in the worst case, can represent a great risk for the patient, particularly when a large amount of the dose is dumped within a short period of time (22,23). Such positive food effects are often the result of the loss of the integrity of matrices or coatings (i.e., devices that control drug release of ER dosage forms).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of dosage form and the intraluminal conditions, a co-administered meal can result in both so-called "positive" and "negative" food effects. Positive food effects typically come along with an increase in drug release from ER formulations and in the worst case, can represent a great risk for the patient, particularly when a large amount of the dose is dumped within a short period of time (22,23). Such positive food effects are often the result of the loss of the integrity of matrices or coatings (i.e., devices that control drug release of ER dosage forms).…”
Section: Introductionmentioning
confidence: 99%
“…This can represent a great risk for the patient, especially in cases when a large amount of the dose is dumped within a short period of time [100,101]. Fats, high concentrations of bile components and pH changes [101,102] are typical triggers for increased drug-release rates.…”
Section: Effect Of Food On Drug Relelasementioning
confidence: 99%
“…This can represent a great risk for the patient, especially in cases when a large amount of the dose is dumped within a short period of time [100,101]. Fats, high concentrations of bile components and pH changes [101,102] are typical triggers for increased drug-release rates. These same factors can cause negative food effects for reasons such as adsorption of food contents, a decrease in luminal diffusivity due to an increase in viscosity in the upper GI tract and changes in the absorption rate due to food-induced changes in GI motility and passage time along the GI tract [103,104].…”
Section: Effect Of Food On Drug Relelasementioning
confidence: 99%
“…Once nightly sustained release theophylline in elderly subjects A recent paper (Steffensen & Pedersen, 1986) has suggested that once nightly sustained release theophylline therapy (Uniphyllin, Napp Laboratories) produces 'very We have studied seven elderly patients (age 69-86, median 80 years) without asthma, in a rehabilitation unit, undergoing active rehabilitation for primarily musculoskeletal problems. None suffered from any significant systemic illness nor was taking any medication currently known to interfere with either absorption or elimination of theophylline.…”
mentioning
confidence: 99%